1994
DOI: 10.1182/blood.v84.5.1415.bloodjournal8451415
|View full text |Cite
|
Sign up to set email alerts
|

Annexin V for flow cytometric detection of phosphatidylserine expression on B cells undergoing apoptosis

Abstract: Apoptosis, or programmed cell death, is a general mechanism for removal of unwanted cells from the immune system. It is characterized by chromatin condensation, a reduction in cell volume, and endonuclease cleavage of DNA into oligonucleosomal length fragments. Apoptosis is also accompanied by a loss of membrane phospholipid asymmetry, resulting in the exposure of phosphatidylserine at the surface of the cell. Expression of phosphatidylserine at the cell surface plays an important role in the recognition and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,862 publications
(94 citation statements)
references
References 0 publications
1
79
0
Order By: Relevance
“…4D) and displayed AV/PI positive staining consistent with apoptosis (Fig. 4D,F,G) 49 . Morphological analysis further indicated that neutrophils cultured for 30 hours presented as a mixture of viable cells and apoptotic cells with condensed and rounded nuclei 50 (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…4D) and displayed AV/PI positive staining consistent with apoptosis (Fig. 4D,F,G) 49 . Morphological analysis further indicated that neutrophils cultured for 30 hours presented as a mixture of viable cells and apoptotic cells with condensed and rounded nuclei 50 (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…If our hypotheses are correct, we would expect perforin to colocalize with exposed PS 28 on the CTL plasma membrane. To test this, we performed confocal microscopy on activated CTLs that were pre-treated with annexin V-Alexa Fluor 568, as a marker for PS exposed on the cell surface 29 . Importantly, this pre-labelling with annexin V ensured detection only of PS already exposed on the CTL membrane before perforin addition, thus avoiding any contribution of PS flip/flop upon perforin association with the plasma membrane 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Organisms evolve the cell suicide mechanism termed apoptosis to eliminate the redundant, damaged, or infected cells. 26 The Annexin V-FITC assay perceives such early apoptotic cells through flow cytometry assay in a cell population. In order to determine whether the cumin nanoemulsion induces cell death by apoptosis, Annexin V-FITC Assay was performed using cumin nanoemulsion at a concentration of 1.5 ”L/mL.…”
Section: Flow Cytometrymentioning
confidence: 99%